2017
DOI: 10.1039/c7gc01709j
|View full text |Cite
|
Sign up to set email alerts
|

One-pot integrated processing of biopolymers to furfurals in molten salt hydrate: understanding synergy in acidity

Abstract: Developed as energy-efficient and integrated method for soluble sugars and furfurals with high yields and high carbon efficiency from polysaccharides and lignocellulosic biomass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 50 publications
1
48
0
Order By: Relevance
“…40 The observation of the effective cleavage of GG under milder conditions (very low acid concentration and moderate temperature, 10 mM HCl and 100°C) in lithium bromide trihydrate was presumably ascribed to (1) the synergy between the acid and LiBr in cleaving the β-O-4-aryl ether bond, and (2) the enhanced acidity of the Brønsted acid in LiBr trihydrate. 47 The aforementioned results demonstrated that both acid and LiBr trihydrate synergistically depolymerized lignin in the ALBTH system under mild conditions. A similar synergistic effect of the acid and LiBr trihydrate in ALBTH was reported in the hydrolysis and dehydration of polysaccharides to furfurals.…”
Section: Reactions Of Lmcs In Albthmentioning
confidence: 87%
See 1 more Smart Citation
“…40 The observation of the effective cleavage of GG under milder conditions (very low acid concentration and moderate temperature, 10 mM HCl and 100°C) in lithium bromide trihydrate was presumably ascribed to (1) the synergy between the acid and LiBr in cleaving the β-O-4-aryl ether bond, and (2) the enhanced acidity of the Brønsted acid in LiBr trihydrate. 47 The aforementioned results demonstrated that both acid and LiBr trihydrate synergistically depolymerized lignin in the ALBTH system under mild conditions. A similar synergistic effect of the acid and LiBr trihydrate in ALBTH was reported in the hydrolysis and dehydration of polysaccharides to furfurals.…”
Section: Reactions Of Lmcs In Albthmentioning
confidence: 87%
“…A similar synergistic effect of the acid and LiBr trihydrate in ALBTH was reported in the hydrolysis and dehydration of polysaccharides to furfurals. 47,48 The structures of the GG products in ALBTH and NLBTH were further characterized by HSQC NMR analysis. HK and BD moieties were detected from the ALBTH-treated GG (Fig.…”
Section: Reactions Of Lmcs In Albthmentioning
confidence: 99%
“…Interestingly, it is well known that molten salt hydrates have excellent ability to dissolve polysaccharides, such as cellulose and hemicellulose, and can be used as media for their hydrolysis, 5 such as cellulose hydrolysis in acidified LiBr molten salt hydrate media 6 and synthesis of furfurals from biopolymers in molten salt hydrate. 7 However, they showed limited ability to dissolve lignin, which provides an opportunity to quantitate lignin in lignocellulosic biomass, such as acidic lithium bromide trihydrate. 8 The key point of efficient utilization of lignocelluloses is their disassembly by a simple and mild method and then conversion of the relative fractions to valuable building block molecules, intermediates, or materials.…”
Section: Introductionmentioning
confidence: 99%
“…Many of the processes for conversion of biomass into fuels or chemicals often employ chemical catalysis or fermentation as an intermediate step to obtain platform molecules. Some platform molecules that have garnered attention are the C 5 and C 6 sugar‐derived aldehydes such as furfural and 5‐hydroxymethylfurfural, which can be produced using homogeneous or heterogeneous catalysis . Similarly, fermentation of sugars can yield short‐chain alcohols, ketones, and carboxylic acids which may also be used as platform molecules.…”
Section: Introductionmentioning
confidence: 99%